Phylogenomic Analysis Reveals Dispersal-Driven Speciation and Divergence with Gene Flow in Lesser Sunda Flying Lizards (Genus Draco). (12th June 2021) - Reilly, Sean B; Stubbs, Alexander L; Arida, Evy; Karin, Benjamin R; Arifin, Umilaela; Kaiser, Hinrich; Bi, Ke; Iskandar, Djoko T; McGuire, Jimmy A
Abstract: The Lesser Sunda Archipelago offers exceptional potential as a model system for studying the dynamics of dispersal-driven diversification. The geographic proximity of the islands suggests the possibility for successful dispersal, but this is countered by the permanence of the marine barriers and extreme intervening currents that are expected to hinder gene flow. Phylogenetic and species delimitation analyses of flying lizards (genus Draco ) using single mitochondrial genes, complete mitochondrial genomes, and exome-capture data sets identified 9–11 deeply divergent lineages including single-island endemics, lineages that span multiple islands, and parapatrically distributed nonsister lineages on the larger islands. Population clustering and PCA confirmed these genetic boundaries with isolation-by-distance playing a role in some islands or island sets. While gdi estimates place most candidate species comparisons in the ambiguous zone, migration estimates suggest 9 or 10 species exist with nuclear introgression detected across some intra-island contact zones. Initial entry of Draco into the archipelago occurred at 5.5–7.5 Ma, with most inter-island colonization events having occurred between 1–3 Ma. Biogeographical model testing favors scenarios integrating geographic distance and historical island connectivity, including an initial stepping-stone dispersal process from the Greater Sunda Shelf through the Sunda Arc as far eastward as Lembata Island. However, rather than reaching the adjacent island of Pantar by dispersing over the 15-km wide Alor Strait, Draco ultimately reached Pantar (and much of the rest of the archipelago) by way of a circuitous route involving at least five overwater dispersal events. These findings suggest that historical geological and oceanographic conditions heavily influenced dispersal pathways and gene flow, which in turn drove species formation and shaped species boundaries. [Biogeography; genomics, Indonesia; lizards; phylogeography; reptiles]